Mostar: Death of a City
ABC Nightline is about fighting between Muslims and Croats over the city of Mostar, one of the most devastated cities in the former Yugoslavia, according to BBC reporter Jeremy Brown. We see much of civilian destruction, injured and dying civilians and children, citizens forced from their home.